Quality by Design (QbD)-Based Numerical and Graphical Optimization Technique for the Development of Osmotic Pump Controlled-Release Metoclopramide HCl Tablets - Farooqi S; Yousuf RI; Shoaib MH; Ahmed K; Ansar S; Husain T (Dove Medical Press, 2020)
Sadaf Farooqi,1 Rabia Ismail Yousuf,1 Muhammad Harris Shoaib,1 Kamran Ahmed,1 Sabah Ansar,2 Tazeen Husain1 1Department of Pharmaceutics, Faculty of Pharmacy and Pharmaceutical Sciences, University of Karachi, Karachi 75270, Pakistan; 2Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, King Saud University, Riyadh 11433, Saudi ArabiaCorrespondence: Rabia Ismail Yousuf; Muhammad Harris ShoaibDepartment of Pharmaceutics, Faculty of Pharmacy and Pharmaceutical Sciences, University of Karachi, Karachi 75270, PakistanEmail rabia_pharmaceutics@yahoo.com; harrisshoaib2000@yahoo.comPurpose: To develop the osmotically controlled-release gastroprokinetic metoclopramide HCl tablets, using quality by design (QbD)-numerical and graphical optimization technique for the treatment of gastroparesis and prophylaxis of delayed nausea and vomiting induced by low-high emetogenic chemotherapy.Methods: Formulations were designed by central composite design using Design Expert version 11.0.0, with osmogen concentration (X1), orifice size (X2), and tablet weight gain after coating (X3) as input and in-vitro drug release at 1hr. (Y1), 6 hrs. (Y2), and 12 hrs. (Y3), and the regression coefficient of drug release data fitted to zero-order, RSQ zero (Y4) as output variables. Core tablets prepared by direct compression were coated with Opadry® CA. The experimental design was validated by the polynomial equation. A correlation between predicted and observed values was evaluated by random checkpoint analysis. The optimized formulations were characterized for drug release, pH effect, osmolarity, agitation intensity, surface morphology, and stability study, and were subjected to accelerated studies according to ICH guidelines.Results: The interaction charts and response surface plots deduced a significant simultaneous effect of X variables on in vitro drug release and RSQ zero. The numerical optimization model predicted > 90% drug release with X1 (13.30%), X2 (0.6 mm), and X3 (7.96%). Random checkpoint analysis showed a good correlation between predicted and observed values. The optimized formulation followed zero-order kinetics (r2=0.9703) drug release. Shelf life calculated was 2.8 years as per ICH guidelines.Conclusion: The QbD-based approach was found successful in developing controlled release osmotic tablets of metoclopramide HCl, for reducing the dosage frequency, better emetic control, and improve patient compliance.Keywords: metoclopramide, elementary osmotic tablet, EOP, central composite design, controlled release, quality by design, QbD, numerical optimization